Contraception for women aged 40 and over. (2nd March 2020) - Boog, Katie; Cooper, Michelle
Abstract : Although fertility naturally declines with age, women who do not wish to become pregnant require contraception until menopause. The safety profile for contraception in women over 40 is different to that of younger women, due to an increased background risk of co-morbidities such as venous thromboembolism, osteoporosis and breast cancer. Conversely, contraception may alleviate or mask symptoms of perimenopause, such as vasomotor symptoms or problematic periods, conferring additional non-contraceptive benefits to women in this age group. For these reasons, the risk-benefit ratio for women over 40 using contraception is different to that of younger women and requires specific consideration when working with women to choose a suitable method of contraception.